Analisis Perencanaan Pembelajaran Menggunakan RPM dalam Kurikulum Merdeka di Sekolah Dasar - Rihadatul Nasywa; Dani Anggara Mulutua Manalu; Lisna Agustin (Lembaga Yasin AlSys, 2026)
Although lesson planning within the Kurikulum Merdeka has been widely examined, studies that specifically address the quality and implementation of Rencana Pembelajaran Mendalam (RPM) at the elementary school level remain limited. This study aimed to analyze the quality of RPM prepared by a Grade IV mathematics teacher by examining its strengths and weaknesses in both design and classroom implementation. A qualitative approach with a single-case study design was employed, involving one Grade IV teacher selected through purposive sampling. Data were collected through semi-structured interviews, document analysis of the RPM and teaching modules, and classroom observations using photos and videos, and were then analyzed using thematic analysis. The findings show that the RPM was systematically developed by integrating a Problem-Based Learning model, the use of concrete and digital media, and a TPACK approach to support deep learning. However, gaps remain between planning and practice, particularly in the implementation of differentiated instruction due to heterogeneous student abilities, limited time, and demands to complete the prescribed content. These findings contribute to the development of constructivist theory and principles of deep learning in the context of the Kurikulum Merdeka, and broaden understanding of lesson planning practices in elementary schools. The study concludes that strengthening teachers’ pedagogical competence and institutional support is essential for optimizing RPM implementation, and recommends continuous professional development programs, particularly in differentiated instruction and the management of classroom dynamics, while also opening opportunities for further research on the direct impact of RPM implementation on student learning outcomes in more diverse school contexts.